Direct Effects of Glyphosate on In Vitro T Helper Cell Differentiation and Cytokine Production - Maddalon, Ambra; Iulini, Martina; Galbiati, Valentina; Colosio, Claudio; Mandić-Rajčević, Stefan; Corsini, Emanuela (Frontiers in Immunology, 2022)
Glyphosate (G) is the active ingredient of the most used herbicides worldwide. Its use is currently very debated, as several studies indicating its hazard and toxicity are emerging. Among them, there is evidence of adverse effects on the immune system. The aim of this work was to investigate if G could directly affect immune cells. Peripheral blood mononuclear cells (PBMC) obtained from healthy donors were used as experimental model. PBMC were expose to G and stimulated with PMA/ionomycin, T helper (Th) cell differentiation and cytokine production were assessed by flow cytometry and enzyme-linked immunosorbent assay, respectively. A reduction of Th1/Th2 ratio, mainly due to a decrease in Th1 cells, was observed following G exposure. Results show an enhancement of IL-4 and IL-17A production, and a reduction of IFN-γ. Based on literature evidence that suggest G being an endocrine disruptor, we investigated the role of nuclear estrogen receptors (ER). ERα/ERβ inhibition by ICI 182,780 abolished the effects of G on IFN-γ and IL-4 release, suggesting a role of ER in the observed effects. To further characterize the mechanism of action of G, miRNAs, both in exosome and intracellular, were investigated. A statistically significant increase in miR-500a-5p was observed following G treatment. The blockage of miR-500a-5p, using a specific antagomir, prevented G-induced reduction of IFN-γ production. Finally a relationship between miR-500a-5p up-regulation and ER was observed. Overall, these results suggest that G can directly act on T cells, altering T cell differentiation and cytokines production.